Chapter 14: Kinetic Theory of Gases - Saifful Kamaluddin, Muzakir (SAP Publications Sdn. Bhd., 2011)
Kinetic theory of gases, assumes that the molecules are very small relative to the distance between molecules. The molecules are in constant, random motion and frequently collide with each other and with the walls of the container. The individual molecules possess the standard physical properties of mass, momentum, and energy. Molecules are very tiny and it is very difficult to measure the properties of each individual molecules. In kinetic theory we describe the physical properties in terms of the measurable physical quantities of the gas a whole.